Community Service Activities: Realizing Sustainable Social Care Through the Kindergartens Togetherness - Kartika Nuringsih; Edalmen Edalmen; Vicly G. Lumingkewas (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
As an effort to realize children's concern for each other, an activity was carried out with the union of parents and teachers at one of the kindergartens in Beji Timur, Depok. This moment continues previous activities with the aim of being a solution to maintain the sustainability of social activities at Raudhatul Athfal Taufiqurrahman. Using participatory action research, the approach involves providing dissemination to children about the importance of sharing with others. The activity was carried out in the month of Ramadan, attended by 30 students with the school principal, accompanying teachers, and representatives of the student’s parents. At this event, the children distributed gifts to orphans and people in need around the school. With this action, children experience sharing with others so that the support of parents and teachers is expected to be touched and interested in social activities. This effort is related to the formation of good character in children so that collaboration with stakeholders will support the sustainability of this education. The togetherness of several parties is a form of subjective norm so that children become more interested in social activities. Meanwhile, messages reminded by teachers and mothers at home can form a positive attitude towards social activities. In this way, children can assess this activity as a positive experience, thereby fostering awareness and prosocial behavior in their adult years. This is in line with the sustainable development goals to ensure development progress for children. As a recommendation, further activities can be carried out with orphanages.